Trivalent Chromium, Iron and Cobalt Complexes of Hydrozones Derived from 2,6-Diacetyl pyridine dihydrazide - SINGH, R.P.; GUPTA, D. (Asian Journal of Chemistry, 2010)
In this study, trivalent chromium, iron and cobalt complexes are synthesized by the reaction of 2,6-diacetyl pyridine dihydrazide (DAPD) and diacetyl in the presence of metal ions. The metal complexes having general composition [M (C13H15N5)X2]X, where M = Cr(III), Fe(III), X = Cl, Br, NO3 or NCS for Cr(III) and Fe(III), X = OH, M = Co(III) were characterized by elemental analysis, conductance, magnetic susceptibility, electronic and infrared spectra studies. On the basis of these studies, Cr(III), Fe(III) and Co(III) complexes has assigned trigonal bipyramidal geometry and found to be high spin.